2017
DOI: 10.1039/c7cp06097a
|View full text |Cite
|
Sign up to set email alerts
|

Pure zero-dimensional Cs4PbBr6 single crystal rhombohedral microdisks with high luminescence and stability

Abstract: Zero-dimensional (0D) perovskite CsPbBr has been speculated to be an efficient solid-state emitter, exhibiting strong luminescense on achieving quantum confinement. Although several groups have reported strong green luminescence from CsPbBr powders and nanocrystals, doubts that the origin of luminescence comes from CsPbBr itself or CsPbBr impurities have been a point of controversy in recent investigations. Herein, we developed a facile one-step solution self-assembly method to synthesize pure zero-dimensional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
84
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(96 citation statements)
references
References 30 publications
12
84
0
Order By: Relevance
“…For instance, no CsPbBr 3 diffractions peaks were reported in various Cs 4 PbBr 6 samples, including powders, single crystals, and NCs. 11,14,17,18,20,21 For instance, De Bastiani et al were able to demonstrate that the presence of any CsPbBr 3 impurity phase down to 0.5% in weight could be detected by XRD (Figure 4a). 21 Nevertheless a similar experiment, in which nonluminescent Cs 4 PbBr 6 NCs were mixed with a small amount (2% molar, 0.5 wt %) of highly luminescent CsPbBr 3 NCs, indicated that this small amount of CsPbBr 3 did not result in any clear CsPbBr 3 features in the XRD pattern (Figure 4b).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, no CsPbBr 3 diffractions peaks were reported in various Cs 4 PbBr 6 samples, including powders, single crystals, and NCs. 11,14,17,18,20,21 For instance, De Bastiani et al were able to demonstrate that the presence of any CsPbBr 3 impurity phase down to 0.5% in weight could be detected by XRD (Figure 4a). 21 Nevertheless a similar experiment, in which nonluminescent Cs 4 PbBr 6 NCs were mixed with a small amount (2% molar, 0.5 wt %) of highly luminescent CsPbBr 3 NCs, indicated that this small amount of CsPbBr 3 did not result in any clear CsPbBr 3 features in the XRD pattern (Figure 4b).…”
mentioning
confidence: 99%
“…For instance, unlike CsPbBr 3 and its hybrid perovskite counterpart, which are usually found to be bromine-deficient, 8083 Cs 4 PbBr 6 is often reported to have a Br:Pb ratio that is usually higher than 6, thus implying that Cs 4 PbBr 6 are rather halide rich. 14,18,20,80 One could therefore expect a rather low density of V Br .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The maximum of the emission spectrum peak locates at 519 nm. Based on the spectra, we can estimate the band gap of Cs 4 PbBr 6 nanoparticles to be 2.4 eV in good agreement with the reported values . We have to state that there was a big discussion about the origin of the PL for this material ,,,,,.…”
Section: Resultsmentioning
confidence: 99%
“…Both performance and fundamental understanding of Cs 4 PbBr 6 have been widely investigated. In addition, temperature dependence of PL of perovskite materials including Cs 4 PbBr 6 nanoparticles has also been reported ,,,. However, temperature‐dependence at single particle level has rarely been reported so far.…”
Section: Introductionmentioning
confidence: 99%